2019
DOI: 10.1002/cssc.201802525
|View full text |Cite
|
Sign up to set email alerts
|

First‐Principles Simulations for Morphology and Structural Evolutions of Catalysts in Oxygen Evolution Reaction

Abstract: to demonstrate how first-principles calculations can predict the morphology of nanoparticles, explore the pathway of electrochemically induced phase transition, and resolve the structure of ah eterojunction. With these new theoretical techniques, the structure-activity relationship of the OER for a complex catalytic system can be determinedw ithoute xperimentali nputs. Such ab ottom-up strategy holds great promise to reveal the active site and mechanism of ac omplex catalytic system from first-principles calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 71 publications
(120 reference statements)
0
31
0
Order By: Relevance
“…Over the past decade, fundamental understanding in electrocatalytic activity has been pushed forward by ab initio methods, although the underlying approximations have hardly been validated against benchmark experiments . Ab initio methods for stability issues in electrocatalytic reactions are just emerging . Therefore, to deepen our understanding of the molecular processes in electrocatalysis (activity and stability), kinetic and structural studies of well‐defined model electrode materials with low structural complexity are required.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past decade, fundamental understanding in electrocatalytic activity has been pushed forward by ab initio methods, although the underlying approximations have hardly been validated against benchmark experiments . Ab initio methods for stability issues in electrocatalytic reactions are just emerging . Therefore, to deepen our understanding of the molecular processes in electrocatalysis (activity and stability), kinetic and structural studies of well‐defined model electrode materials with low structural complexity are required.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Ab initio methods for stability issues in electrocatalytic reactions are just emerging. [12][13][14][15] Therefore, to deepen our understanding of the molecular processes in electrocatalysis (activity and stability), kinetic and structural studies of well-defined model electrode materials with low structural complexity are required. These experiments can ultimately serve as benchmarks for theoretical ab initio methods, thereby allowing to validate and to advance the theoretical methodology.…”
Section: Introductionmentioning
confidence: 99%
“…However, an evaluation of the activity close to zero overpotential is especially for many-electron transfer processes, such as oxygen evolution or reduction, [65][66][67] not practicable, which might explain that in certain cases activity trends cannot be correctly predicted by the prototypical activity-based volcano approach. [27][28][29][30] Here, advanced concepts that go beyond the conventional activity-based volcano approach and include the applied overpotential into the analysis are called for in the future to improve material optimization within a class of materials, such as the construction of overpotential-dependent Volcano plots as suggested by the author only recently. [68] The activity-stability volcano plot indicates that the active RuO 2 (110)-O ot configuration (cf.…”
Section: Discussion Of Activity-stability Volcano Plotsmentioning
confidence: 99%
“…Despite of the fact that this straightforward approach has spurred research in various fields of catalysis, recently critical remarks concerning the reliability of the traditional volcano approach increased, as it was demonstrated that in certain cases conventional activity-based volcano plots were not able to reproduce activity trends of electrocatalysts correctly. [27][28][29][30] This finding might be traced to the underlying assumptions within the volcano concept: on the one hand, the activity of electrocatalysts is estimated at zero overpotential based on a combination of Sabatier's principle and the Brønsted-Evans Polanyi (BEP) relation, which couples thermodynamics with kinetics by stipulating that changes in the transition state free energy (kinetics) follow alternations in the free energy change (thermodynamics). [31] Hitherto, the applied overpotential is not included into the analysis, even though electrocatalytic reactions are exergonic only if an overpotential is exerted.…”
Section: Introductionmentioning
confidence: 99%
“…[109][110][111][112] Nonetheless,o ne should keep in mind that volcanop lotsd on ot depictar eal activity,i n terms of at ransition-statef ree energy on the y axis, [12] buti nstead at hermodynamic quantity serves as am easure for the underlying kinetics. For small values of DG 0 (O ot ) (strong oxygen bonding), the Volmer step (adsorption of chloride) is reconciled as the (kinetically) limiting reaction step, whereas, for large values of DG 0 (O ot )( weak oxygen bonding), the Heyrovsky step is (kinetically) hampered.W ithin this discussion, the free-energy changeo ft he Volmer or Heyrovsky step is relatedt oa ctivity of the electrocatalyst by the Brønsted-Evans-Polanyi (BEP) relationship,w hich stipulates that changes in the transition-state free energy (kinetics) follow alterations in the energy change (thermodynamics), thereby coupling thermodynamics and kinetics.…”
Section: Catalysismentioning
confidence: 99%